Statistics of Industrial Protectionism. Part I: The Formation of Organizational and Institutional Mechanisms - Krekhivskyi, O. V. (Statistics of Ukraine, 2023)
Numerous decisions made by the Ukrainian government in the conditions of a state of war require high-quality data. Among the identified priorities for the recovery of the domestic economy is the development of strategic industries, the implementation of which will necessitate new state decisions, along with statistical data to assess their outcomes. Historical parallels between the situation at the beginning of the 20th century and recent events serve as the basis for the assumption that the answer to the question of "How to accelerate the economic recovery of Ukraine?" should be sought not in the analysis of contemporary policies in developed countries but primarily in the investigation of retrospective mechanisms that facilitated the growth of existing industries and the creation of new ones. The aim of the article is to examine historical facts related to the implementation of industrial protectionism in the challenging conditions of war and post-war recovery in Great Britain. It seeks to identify the organizational and institutional mechanisms of the statistical system that facilitated the implementation and assessment of the outcomes of such decisions. Furthermore, the article aims to formulate conclusions that can be applied to Ukraine. It has been established that the First World War was a pivotal moment in the economic policy of Great Britain, directing it towards protectionism. The catalyst for this shift was the realization that critical national industries were in a precarious state due to the lack of imported supplies of various goods, mainly synthetic dyes and chemical ingredients, upon which the economy and security depended. This prompted the country’s parliament and government to regulate industry and implement tools of state aid and protection against foreign competitors. Along with this, it led to organizational and institutional changes in the statistical system, as well as shifts in the directions and methodological approaches to monitoring the obtained results and the actual introduction of statistics related to industrial protectionism. It has been demonstrated that historical parallels during the COVID-19 pandemic are evident in terms of both the identified dependencies on the import of active pharmaceutical ingredients and other substances (two-thirds of production concentrated in China) and the government’s actions to address the situation and changes in statistics. Drawing from the experience of Great Britain, it is justified that the introduction of measures to develop strategic sectors in Ukraine, accompanied by state incentives and protective tariffs, necessitates the modernization of the organizational and institutional mechanisms of the national statistical system. A component of these processes should be the digitization of functions assigned to the State Statistics Service of Ukraine, which would allow for obtaining high-quality operational data for both decision-making and evaluating their outcomes.